2008
DOI: 10.1080/14767050801924431
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum fetal ECG and diabetes

Abstract: ST depression on the FECG was significantly more prevalent in the fetuses of mothers with DM, probably not indicating hypoxia but an altered ability of the myocardium to respond to the stress of labour. Further studies into the mechanism of fetal compromise during diabetic labour, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
3
19
1
Order By: Relevance
“…On fetal ECG, ST depression was significantly more prevalent in fetuses of diabetic mothers, as demonstrated by Yli et al 26 In children with a mean hemoglobin A Ͼ10%, a reduction in heart rate variability was predictive for onset of symptomatic neuropathy. 27 Shiono et al 28 studied children and adolescents aged 7 to 20 years with poor glycemic control (hemoglobin A 1c Ն10%) with signal-averaged ECG; the authors found a prolonged filtered QRS duration and a significantly low root mean square voltage, demonstrating subclinical cardiac impairment.…”
Section: Fetal and Childhood Ecg Signs In Diabetes Mellitusmentioning
confidence: 53%
“…On fetal ECG, ST depression was significantly more prevalent in fetuses of diabetic mothers, as demonstrated by Yli et al 26 In children with a mean hemoglobin A Ͼ10%, a reduction in heart rate variability was predictive for onset of symptomatic neuropathy. 27 Shiono et al 28 studied children and adolescents aged 7 to 20 years with poor glycemic control (hemoglobin A 1c Ն10%) with signal-averaged ECG; the authors found a prolonged filtered QRS duration and a significantly low root mean square voltage, demonstrating subclinical cardiac impairment.…”
Section: Fetal and Childhood Ecg Signs In Diabetes Mellitusmentioning
confidence: 53%
“…However, in gestational diabetes there may be fetal diastolic dysfunction independent of hypertrophy (2). In diabetic pregnancies, fetal lactic acidosis and hypoxia have both been reported near term, and bradycardic episodes, ST segment depression, and fetal acidemia have been observed during labor in fetuses of both gestational and pregestational diabetic mothers (31,37,38), as well as heart failure with abnormal ECG during labor (19). An increased incidence of fetal bradycardic responses to fetal stress occurs in women demonstrating high anxiety during pregnancy (20).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…37 (Figure 4). Yli and colleagues 38 more frequent occurrence of ST depression in fetuses from mothers with diabetes mellitus, a disorder known to be associated with fetal myocardial dystrophy. 38 The relationship between gestational age and hypoxia has recently been elucidated by Mallard et al, Perinatal Centre, University of Gothenburg, by observing the type of ST patterns emerging in connection with cord occlusion and endotoxin administration in the mid gestation fetal lamb.…”
Section: St Depression -Biphasic St Changesmentioning
confidence: 96%